A new parameter adaptive control of four-dimensional hyperchaotic system. (October 2020) - Liao, Xiaokang; Chen, Zili; Lin, Jianhui
Abstract: By adding a state feedback controller to a three-dimensional chaotic system, a new four-dimensional hyperchaotic autonomous system is constructed. The nonlinear dynamic behavior of the system is deeply investigated, including power spectrum, Poincare cross section, Lyapunov exponential spectrum and bifurcation graph. The analysis shows that the new four-dimensional hyperchaotic system has complex chaotic motions with different parameters, and the related analog chaotic circuits are designed. Finally, a parameter adaptive controller is designed to achieve global stability control of chaotic systems. The effectiveness of the proposed method is verified by numerical simulation.